2019
DOI: 10.1111/ejn.14520
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oxytocin‐family peptides and substance P on locomotor activity and filial preferences in visually naïve chicks

Abstract: Nonapeptides from the vasopressin/oxytocin family have been implicated in a wide variety of social behaviours across vertebrates. Experimental manipulations that alter nonapeptide levels or receptor function in the brain have provided evidence for understanding how nonapeptides influence responses to social stimuli in adults. While behaviours in adults have been extensively studied, much less in known about roles of nonapeptides in early life and the development of affiliative social behaviours. We examined an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 96 publications
1
12
0
Order By: Relevance
“…A recent study investigated the role of vasotocin and mesotocin (the avian homologs of vasopressin and oxytocin) in mediating the social predisposition for hen-like objects. This revealed that intracranial mesotocin administration increased the level of preference for the stuffed fowl model compared to saline-injected controls (Loveland, Stewart, & Vallortigara, 2019). This suggests that mesotocin signalling may regulate the expression of social predispositions, probably acting on areas of the social behaviour network.…”
Section: The Study Of Early Predispositions As Adaptive Responsesmentioning
confidence: 86%
See 1 more Smart Citation
“…A recent study investigated the role of vasotocin and mesotocin (the avian homologs of vasopressin and oxytocin) in mediating the social predisposition for hen-like objects. This revealed that intracranial mesotocin administration increased the level of preference for the stuffed fowl model compared to saline-injected controls (Loveland, Stewart, & Vallortigara, 2019). This suggests that mesotocin signalling may regulate the expression of social predispositions, probably acting on areas of the social behaviour network.…”
Section: The Study Of Early Predispositions As Adaptive Responsesmentioning
confidence: 86%
“…This is mostly due to the advantages of precocial animals that respond to behavioural tests immediately after birth, as well as to the opportunity to investigate the fast learning mechanism of filial imprinting. These advantages allowed researchers to shed some light on the neural and physiological bases of the early mechanisms (e.g., Horn, 2004;Lorenzi et al, 2017;Loveland et al, 2019;Mayer et al, 2016Mayer et al, , 2017aMayer et al, , 2017bMayer et al, , 2019, including those for the opening and closing of sensitive periods (Aoki et al, 2018;Yamaguchi et al, 2012). While the notion of sensitive period has been traditionally applied to filial imprinting, mounting evidence shows that specific time windows regulate the emergence of predispositions too (e.g., (Bolhuis & Horn, 1997;Bolhuis et al, 1989;Davies, Johnson, & Horn, 1992;Johnson, Davies & Horn, 1989;Miura et al, 2020;Versace, Ragusa & Vallortigara, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…3; n = 8 animals per group, four independent experiments), like the dopamine receptors (DRD1 and DRD2) together with the DA responsive protein DARPP32, the serotonin receptors (5HTR1A and 5HTR2A) with the serotonin transporter 5HTT and genes involved in synaptic plasticity coding for the NMDA subunits (GRIN2A and GRIN2B), and CREB1. We also measured the expression levels of the mesotocin receptor (OXTR) the avian homolog of oxytocin, since the lateral part of the septum is known to receive consistent oxytocinergic innervation (Loveland et al, 2019;Horiai et al, 2020). We again used linear mixed models to evaluate the effect of treatment (CTRL vs VPA), DA subgroup (SN vs VPA) and transcripts, and found that the best fitting model was a random slopes and intercepts model with the same parameters used for analysis of gene expression in the mesencephalon.…”
Section: Resultsmentioning
confidence: 99%
“…In chickens, these regions are thought to be important for filial imprinting (Aoki et al, 2015;Nakamuri et al, 2010), a form of early learning that, like song learning, takes place during a sensitive period. In mammals as well as in birds, imprinting is part of an overarching model of experience-dependent brain development in which early attachment, proximity-seeking, and social orienting are regulated by oxytocin (Hammock, 2015(Hammock, , 2018Loveland et al, 2019). Because song learning in zebra finches depends critically on such processes, (Adret, 1993;Baran, 2017;Rodríguez-Saltos, 2017), this species represents powerful opportunities to understand the role of oxytocin in socially guided vocal development.…”
Section: Overview Of Findingsmentioning
confidence: 99%